CRYPTO-EXCHANGES IN NIGERIA: A REVIEW OF THE REGULATORY FRAMEWORK. - Aliyu Abdullahi (ABUAD Law Journal, 2024)
Regulating the exchange market in Nigeria seemed seamless until the coming of blockchain technology powered by smart contract. The blockchain platform spawned the idea for the trading of digital assets which by their nature could not be traded on the regular exchanges. This raises two major inquiries which are, to what securities silos are the digital assets be classified and whether trading digital assets on the blockchain platform requires special governing rules inform of codes or algorithms as substitute or in addition to the Investment and Securities Act herein after called the Act. To brace up with this new technology, the Nigerian Federal Government issued the National Policy on Digital Economy to regulate the digital economy generally in the country and formulated the National Blockchain Policy in particular. Additionally, the Security and Exchange Commission pursuant to Section 13 (o),(dd) of the Act issued Rules on Issuance, Offering and Custody of Digital Assets, to specifically regulate transactions of digital assets on the crypto-exchanges. Adopting doctrinal method of research, this paper examines the law and policy frameworks for the regulation of crypto-exchange in Nigeria with the sole objective of ascertaining the propriety and robustness of the issued instruments to regulate the crypto-exchange. The paper finds inter alia that neither the Act nor the issued Rules on Issuance, Offering and Custody of Digital Assets is sufficient to regulate digital assets transactions on the blockchain platform. Thus, the paper recommends hybrid of the regulatory governance to include codes, algorithms and the Act.